Efeitos do exercício aeróbio na osteoartrite de joelho induzida por transecção do ligamento cruzado anterior em ratos - Milares, Luiz Paulo Gomes Rosa [UNIFESP] (2015)
Osteoarthritis (OA) is a chronic, degenerative joint disease which can cause a significant locomotor disability, especially in the elderly population. Aerobic exercise has been shown in non-drug therapy, however, the mechanisms triggered by this feature are still not well understood. The aim of this study was to evaluate the effects of aerobic exercise in a moderate intensity on knee joint cartilage of rats subjected to an experimental model of osteoarthritis induced by anterior cruciate ligament transection (ACLT). 30 wistar rats, male, were used and separated into 3 groups (n=10) were control (CG); osteoarthritic (OAC); osteoarthritic and aerobic exercise (OAT). Treatments were perfomed 4 weeks after surger y. The protocol was aerobic exercise on a treadmill (speed of 16 m/min, 50 min, 3 times per week) for 8 weeks. Morphological and morphometric analysis of cartilage (cellularity, thickness, density of chondrocytes) and protein expression of IL-1?, Caspase-3 and MMP-13 were perfomed. The group submitted to physical exercise presented a change in the morphological organization, lower grade in lesion degree of analysis by Osteoarthritis Reseach Society International, chondrocyte density GOT analysis showed similar results to the OA group, the GOT was significantly thicker articular cartilage in addition to reduction IL-1?, Caspase-3 and MMP-13 expression. Therefore, aerobic exercise in a moderate intensity produced changes in articular cartilage.